Epidemiological Mapping of Human Onchocerciasis in Transmission Suspected Districts of Bale, Borena, and West Arsi Zones of Eastern Ethiopia - Sindew Mekasha Feleke; Gemechu Tadesse; Kalkidan Mekete; Afework Hailemariam Tekle; Amha Kebede (Interdisciplinary Perspectives on Infectious Diseases)
Onchocerciasis is mainly found in western part of Ethiopia and there is no evidence of transmission in the east ward. However, some zones (Bale, Borena, and West Arsi) are suspected for transmission given the area has fast flowing rivers and is covered with vegetation. Therefore, this study was conducted to map onchocerciasis transmission in those zones. About 19 villages were selected based on proximity to the rivers, representation of districts, zones, and vegetation covers, whereas the study participants, all village residents of age > 5 years with good health condition, were skin sniped and examined using microscopy. In this study a total of 2560 study participants were surveyed of which 1332 were female (52%) and 122 were male (48%). The age group of 21–30 years was highest (34.4%) and that of age > 51 years was the lowest (3.1%) study participants. The survey result revealed that none of the study participants regardless of age, sex, and location demonstrated skin snip Onchocerca microfilariae. The prevalence of microfilariae and community microfilarial load (CMFL) were 0% and 0 mf/s, respectively. The finding implied that there is no onchocerciasis in the area and, therefore, there is no need for interventions. Black fly distribution, cytotaxonomic study, and intraborder cross transmission monitoring are recommended.